Risk identification and allocation in underground rail construction joint ventures: contractors’ perspective - Hwang, Bon-Gang; Zhao, Xianbo; Yu, Gwendolyn Shiyu (Journal of Civil Engineering and Management, 2016)
International construction joint ventures (ICJVs) have been widely used in large-scale infrastructure projects all over the world. This study aims to investigate the factors affecting adoption of ICJVs for underground rail construction projects, to identify the critical risks faced by parties that perform the projects under ICJVs, and to examine the obstacles to appropriate risk allocation among the parties under ICJVs. To achieve these objectives, an in-depth literature review was carried out and a questionnaire survey was conducted with 33 contractor firms as well. The survey results reported “sharing of project risks” as the top attractive factor of ICJVs and “differences in culture and working style” as the top negative factor. In addition, both foreign and local contractors considered “partners disagree over some conditions in contract” the most critical risk to the parties involving projects under ICJVs. While risk allocation was perceived to be very important for ICJVs, “unclear division of responsibilities and risks” and “differences in culture and working styles” could be the most significant obstacles against effective risk allocation among the parties. The findings from this study will help improve the implementation of ICJVs and provide valuable information for organizations who intend to participate in ICJVs in Singapore.